Acanthamoeba castellanii as a model for unveiling Campylobacter jejuni host–pathogen dynamics - Nasher, Fauzy; Lehri, Burhan; Stabler, Richard A.; Wren, Brendan W. (Frontiers in Cellular and Infection Microbiology, 2025)
The persistence of the major enteric pathogen Campylobacter jejuni in the natural environment, despite being microaerophilic, remains unsolved. Its survival in the natural atmospheric environment likely stems from several factors, including interactions with amoebae. C. jejuni transiently interacts with Acanthamoeba, and this is thought to provide protection against unfavorable atmospheric conditions and subsequently prime the bacteria for interactions with warm-blooded hosts. Acanthamoeba play vital roles in microbial ecosystems by preying on bacterial species, some of which are clinically important. We analyzed the whole transcriptome of A. castellanii infected with C. jejuni 11168H. Our findings provide evidence that infection of A. castellanii with C. jejuni triggers distinct and reproducible cellular responses. Upregulated genes were associated with protein synthesis, DNA damage and repair, gluconeogenic pathways, and protein folding and targeting, while downregulated genes were involved in calcium ion transport, osmotic stress response, energy reserve metabolic processes, and protein hydroxylation. From these data, we characterized Cj0979c, named here C. jejuni endonuclease (CjeN), which induces DNA damage in A. castellanii. High-resolution microscopy revealed an unexpected association between C. jejuni and host mitochondria, while infected cells show elevated cytosolic calcium levels and metabolic changes favoring “Warburg-like” metabolism. A. castellanii cells showed increased lactate production, which was subsequently depleted, suggesting that this host metabolic by-product may support C. jejuni survival. These findings identify an unexpected interaction between amoebae and a microaerophilic bacterium and provides a useful model for further research on host–pathogen interactions.